Doxycycline, Azithromycin and Vitamin C (DAV): A potent combination therapy for targeting mitochondria and eradicating cancer stem cells (CSCs) - Fiorillo, Marco; Tóth, Fanni; Sotgia, Federica; Lisanti, Michael P (Aging (Albany, NY.), 2019)
Here, we devised a new strategy for eradicating cancer stem cells (CSCs), via a "synthetic-metabolic" approach, involving two FDA-approved antibiotics and a dietary vitamin supplement. This approach was designed to induce a "rho-zero-like" phenotype in cancer cells. This strategy effectively results in the synergistic eradication of CSCs, using vanishingly small quantities of two antibiotics. The 2 metabolic targets are i) the large mitochondrial ribosome and ii) the small mitochondrial ribosome. Azithromycin inhibits the large mitochondrial ribosome as an off-target side-effect. In addition, Doxycycline inhibits the small mitochondrial ribosome as an off-target side-effect. Vitamin C acts as a mild pro-oxidant, which can produce free radicals and, as a consequence, induces mitochondrial biogenesis. Remarkably, treatment with a combination of Doxycycline (1 μM), Azithromycin (1 μM) plus Vitamin C (250 μM) very potently inhibited CSC propagation by >90%, using the MCF7 ER(+) breast cancer cell line as a model system. The strong inhibitory effects of this DAV triple combination therapy on mitochondrial oxygen consumption and ATP production were directly validated using metabolic flux analysis. Therefore, the induction of mitochondrial biogenesis due to mild oxidative stress, coupled with inhibition of mitochondrial protein translation, may be a new promising therapeutic anti-cancer strategy. Consistent with these assertions, Vitamin C is known to be highly concentrated within mitochondria, by a specific transporter, namely SVCT2, in a sodium-coupled manner. Also, the concentrations of antibiotics used here represent sub-antimicrobial levels of Doxycycline and Azithromycin, thereby avoiding the potential problems associated with antibiotic resistance. Finally, we also discuss possible implications for improving health-span and life-span, as Azithromycin is an anti-aging drug that behaves as a senolytic, which selectively kills and removes senescent fibroblasts.